Analisis Aspek Dampak Lingkungan Hidup “Usaha Petis Ikan” Di Pasongsongan Sumenep Dalam Perspektif Studi Kelayakan Bisnis - Akh Jazuli; Abdur Rohman (Jurnal Manajemen Kreatif dan Inovasi, 2024)
The purpose of this study is to determine the environmental impact caused by fish sauce production activities in Pasongsongan Sumenep. This research uses descriptive qualitative method. Data collection in this study used observation interview techniques, and literature studies. This research uses two types of data, namely primary data and secondary data. The research object was taken in Pasongsongan Village, Sumenep Regency. The results of this study state that the fish paste processing business located in Pasongsongan Sumenep has an impact on the surrounding environment. The impact is in the form of air pollution caused by the process of cooking fish sauce and soil pollution caused by used water washing fish. In addition to the negative impact on the environment, there is also a positive impact, namely providing employment for the community or local residents. To overcome the environmental impact caused by reforesting the land polluted by water used to wash fish. The conclusion of this research is that the fish sauce business has positive and negative impacts on the environment.